FK506 Induces the TGF-β1/Smad 3 Pathway Independently of Calcineurin Inhibition to Prevent Intervertebral Disk Degeneration - Ge, Jun; Wang, Yingjie; Yan, Qi; Wu, Cenhao; Yu, Hao; Yang, Huilin; Zou, Jun (Frontiers in Cell and Developmental Biology, 2020)
Background: Intervertebral disc (IVD) degeneration is the most common cause of lower back pain. Inhibiting inflammation is a key strategy for delaying IVD degeneration. FK506 is a potent immunosuppressive agent that is also beneficial to chondrocytes. However, the potential function of FK506 in IVD and the underlying mechanisms remain unknown. The current study is aim at exploring the underlying mechanism of FK506 in preventing IVD degeneration. Methods: Cell morphology was imaged using an optical microscope. mRNA levels of nucleus pulposus matrix components were determined by qPCR, and protein expression nucleus pulposus matrix components was assessed by western blotting. A rat caudal intervertebral disc degeneration model was established to test for FK506 in vivo. Results: FK506 improved the morphology of nucleus pulposus cells and the cell function at both the mRNA and protein level. FK506 could attenuate nucleus pulposus degeneration induced by IL-1β. Furthermore, FK506 exerted its function via TGFβ/Smad3 activation instead of through CN inhibition. Inhibition of the TGF-β pathway prevented the protective effect of FK506 on IVD degeneration. In an in vivo study, FK506 injection reversed the development of rat caudal IVD degeneration influenced by Smad3. Conclusions: Our current study demonstrates the positive effect of FK506 on delaying the degeneration of IVD via the TGFβ/Smad3 pathway.